Implementasi Program Kelompok Tani Jaya Pada Pengelolaan Kotoran Ternak Sapi Untuk Meningkatkan Pendapatan Masyarakat di Kabupaten Batu Bara - Sitorus, Egi Hermawan; Putra, Ilham Mirzaya (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Livestock productivity must pay close attention to the treatment of the waste produced. Animals excrement created from the outcome of domesticated animals business can be overseen into treated the soil natural manure that can be utilized to increment ecological conveying energy, increment plant creation, and increment the pay of dairy cattle ranchers in selling the fertilizer waste to compost processors. This study intends to distinguish the execution of the dairy cattle excrement handling program into manure and the advancement of making granule compost by the Jaya Rancher Gathering. The examination technique utilized is subjective exploration with an elucidating approach. The examination was led in Sipare-pare Manor Town, Batu Bara Rule, Sei Suka Locale. This exploration included 3 sources. Information assortment is finished through perception, interviews, documentation. The information examination strategies utilized were information decrease, information show, end drawing and triangulation information legitimacy procedures. The results showed that for working farmers, making compost fertilizer is an effective way to increase their monthly income besides raising livestock. The innovation of making granule fertilizers is hampered by experts in the use of granulator machines and the manufacturing process.